Evaluation on Accessibility and Usage of Information and Communication Technology (ICT): Insights from Smallholders in Johor, Malaysia - Nadzifah, Yaakub; Amirul Arif, Ab Aziz; Fazleen, Abdul Fatah (2018)
In today’s age of modernization, Information and Communication Technology (ICT) has played a very important role in the development of agriculture sector. This technology has brought a significant change in agricultural development where farmers can directly communi-cate with traders, government, buyers, and producers. However, due to lack of knowledge and information, farmers are not getting the benefits from these technologies. To understand this, a study was conducted to find out the level of accessibility of ICTs among small-holder farmers. To further understand this issue, the study aims to determine the determinants or critical factors that influence the level of ICT accessibility among oil palm smallholders. A random sampling technique was used to select a total of 85 smallholders in the study area while an administered structured interview schedule on the selected respondents were used for data collection. Frequency counts, percentages and a multiple regression analysis were used in the data analysis. Results revealed that majority of the respondents were males (96.5%), a high percentage (71.8%) chose to use personal computer as their ICT tools while 24% used mobile phone to get access or gain more agricultural and inputs information. The paper concluded that network factor and socio-economics such as age and educa-tional level were the most significant factors that influenced the accessibility of ICTs among oil palm smallholders in Johor, West Ma-laysia.